2010
DOI: 10.4049/jimmunol.1001544
|View full text |Cite
|
Sign up to set email alerts
|

Autoamplification of Notch Signaling in Macrophages by TLR-Induced and RBP-J–Dependent Induction of Jagged1

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
106
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 56 publications
6
106
1
6
Order By: Relevance
“…A recent study by Foldi et al demonstrated that stimulation with TLR agonists led to upregulation of the Notch ligand Jagged1, which is mediated by NF-kB. 16 The authors suggested that this event initiates the Notch signaling cascade during a pro-inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Foldi et al demonstrated that stimulation with TLR agonists led to upregulation of the Notch ligand Jagged1, which is mediated by NF-kB. 16 The authors suggested that this event initiates the Notch signaling cascade during a pro-inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling is reported to activate the NF-kB pathway, and in turn, the NF-kB pathway sustains the activation of Notch signaling via the induction of Notch ligands. 16,18,19 In addition, Notch and NF-kB may cooperatively bind Notch signaling partially regulates IL-6 expression in macrophages W Wongchana and T Palaga 160…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Activation of Notch signaling regulates proinflammatory responses. 22,24 Furthermore, it has been reported that in macrophages infected with Bacillus Calmette-Guérin (BCG), Notch1 is upregulated and SOCS3 expression is induced. 25 Mycobacterial infection also induces the expression of dll4, a Notch ligand, via TLR9 and promotes TH17 activity during granuloma formation.…”
Section: Introductionmentioning
confidence: 99%
“…Among the nine gene-signatures found by our new method (JAG1, MET, CDH5, ABCC3, DSP, ABCD3, PECAM1, MAPRE2 and PDF5), proteins encoded by some of these gene-signatures (e.g., JAG1 and MAPRE2) have been showed to involve in the signal transduction of cells and proliferation control of normal cells [18]. It has also been found that MAPRE2 is highly expressed in pancreatic cancer cells, and seems to be involved in perineural invasion [19].…”
Section: Introductionmentioning
confidence: 99%